Kepemimpinan Digital Kepala Sekolah dalam Memperkuat Ekosistem Pembelajaran di Era Kurikulum Merdeka di Sekolah Dasar - Yulia Septi Wahyuni; Raisa Berlian; Yesika Novita Rahmi (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2025)
The digital leadership of school principals plays a crucial role in strengthening the learning ecosystem in the era of the Merdeka Curriculum, especially in primary schools that are adapting to the use of educational technology. The Merdeka Curriculum emphasizes flexibility, project-based learning, and the use of digital tools to support more independent and meaningful learning processes. In this context, school principals act as digital leaders who not only manage schools but also guide the technological vision, enhance teacher competencies, and foster an innovative and responsive school culture in line with digital developments.This study employed a quantitative descriptive approach through surveys conducted with 120 primary school teachers across three districts/cities. The findings revealed three key results. First, 78% of teachers reported an improvement in their competency in using learning applications following the implementation of digital leadership policies by school principals. Second, 72% of schools reported increased collaboration between teachers and parents through school digital platforms, which positively impacted student engagement in learning. Third, 81% of principals utilized digital data (learning dashboards, online assessments, and daily reports) for faster decision-making regarding students’ learning needs. These findings reinforce that digital leadership significantly contributes to the successful implementation of the Merdeka Curriculum and creates a learning ecosystem that is inclusive, adaptive, and relevant to the demands of 21st-century education.